Isolation and characterization of a Methyl Red-Degrading Pseudomonas sp. from Contaminated Soil (Journal of Environmental Microbiology and Toxicology, 2025)
Microbial-based bioremediation is a greener dye removal method than physicochemical methods like coagulation-flocculation, adsorption, membrane filtration, and advanced oxidation. In this study, we isolated and characterized a methyl red-degrading Pseudomonas sp. from contaminated soil, examining its growth and degradation under different environmental conditions. The bacterium, tentatively designated as Pseudomonas sp. strain Aft-12 demonstrated strong methyl red decolorization capacity. Time-course growth analysis in minimal salt medium supplemented with 200 mg/L methyl red, glucose as a carbon source, and ammonium sulphate as a nitrogen source revealed a minimal lag phase (~12 h), followed by rapid exponential growth and decolorization, reaching completion by 72 h. Strain Aft-12 performed effectively across a range of conditions, showing optimal growth between pH 6.5 and 7.0 and between 30 and 35 °C. Growth was optimal at dye concentrations of between 200 and  250 mg/L. Co-substrate screening revealed that glucose and sucrose significantly enhanced biomass, although Aft-12 maintained activity without supplementation. Azoreductase activity peaked at 1 µmol/min/mg protein after 48 h, supporting enzymatic decolorization via reductive cleavage. These characteristics make this bacterium a promising candidate for sustainable bioremediation of azo dye-laden effluents.
Keywords: Pseudomonas sp. Aft-12; Methyl red decolorization; Azoreductase activity; Textile wastewater bioremediation; Minimal salt medium